2003
DOI: 10.1097/00002030-200311070-00013
|View full text |Cite
|
Sign up to set email alerts
|

Costs of medical services for patients with HIV/AIDS in Khon Kaen, Thailand

Abstract: A large increase in the budget would be required to provide HAART to all adult patients with AIDS under UC. However, the sensitivity analysis showed it would be an affordable policy option if low-cost antiretroviral drugs were successfully introduced. This type of analysis would be useful to assess the financial implications of providing HAART in public health systems worldwide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…The cost per outpatient hospital visit for PLWH in Thailand was $27 [53], again very close to the cost per ProTEST clinic visit. The daily cost of hospice care is shown to be within the range of in-patient hospital cost for AIDS patients in low-income African countries, ranging from $9 to $49.…”
Section: Discussionmentioning
confidence: 91%
“…The cost per outpatient hospital visit for PLWH in Thailand was $27 [53], again very close to the cost per ProTEST clinic visit. The daily cost of hospice care is shown to be within the range of in-patient hospital cost for AIDS patients in low-income African countries, ranging from $9 to $49.…”
Section: Discussionmentioning
confidence: 91%
“…[22, 2428] Studies for lower-middle-income countries (LMIC) were found for India [29, 30] , Lesotho [18] , Morocco [31] , Nigeria [32, 33] , and Thailand [34] ; the median cost of ART was $932 (mean $1,246, range $156 to $3,904) (tables II & IV). In upper-middle-income countries (UMIC), Brazil [23, 35] , Mexico [3638] and South Africa [21, 3945] the median ART cost was $1,454 (mean $2,783; range $1,230 to $5,667) (tables III & IV).…”
Section: Resultsmentioning
confidence: 99%
“…While this has led to reduced hospitalization costs, ART has become the main driver of the total cost of caring for PLWHA. This represents a challenge in low-income countries [ 3 ], emerging economies [ 4 , 5 ] as well as in developed countries [ 6 , 7 ]. The price of HIV care can quickly become a considerable economic burden especially in settings where all drugs are not available free of charge, where they remain on charge by the patients or where direct out of pocket payments (OOPs) are required [ 8 ].…”
Section: Introductionmentioning
confidence: 99%